2011
DOI: 10.1349/ps1.1537-0852.a.389
|View full text |Cite
|
Sign up to set email alerts
|

The Intonation Patterns of Interrogatives in Persian

Abstract: This paper investigates the intonational properties of different types of interrogatives in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(36 citation statements)
references
References 44 publications
(29 reference statements)
2
34
0
Order By: Relevance
“…An IP is marked by a low or high right boundary tone (L% or H%). Within each IP, the materials following the final AP's pitch accent undergo deaccentuation in most sentence types (Sadat-Tehrani, 2011;Rahmani, Rietveld, and Gussenhoven, 2016) or post focal compression (Taheri-Aardali and Xu, 2012;Taheri-Ardali, Rahmani, and Xu, 2014). The prosodic structure of Persian declaratives is illustrated in example (1) and Figure 1 for a typical SOV sentence.…”
Section: Introductionmentioning
confidence: 99%
“…An IP is marked by a low or high right boundary tone (L% or H%). Within each IP, the materials following the final AP's pitch accent undergo deaccentuation in most sentence types (Sadat-Tehrani, 2011;Rahmani, Rietveld, and Gussenhoven, 2016) or post focal compression (Taheri-Aardali and Xu, 2012;Taheri-Ardali, Rahmani, and Xu, 2014). The prosodic structure of Persian declaratives is illustrated in example (1) and Figure 1 for a typical SOV sentence.…”
Section: Introductionmentioning
confidence: 99%
“…Eighty‐one percent (242/298) of the samples did not exhibit the DS high AP boundary tone. Of these, the majority (90%) had the same intonation as the lab speech version (studied in Sadat‐Tehrani ) and had a final rise, with a few (10%) not showing this rise. An example of a typical final‐rising spontaneous YNQ, identical to a read YNQ, is provided in (3)/Figure .…”
Section: Resultsmentioning
confidence: 98%
“…Hermann (1942) argued that interrogatives are universally marked by the presence of a high pitch somewhere in the sentence. Subsequent studies demonstrated that high pitch may manifest itself both locally, for example, in the initial, medial, or final portion of the sentence (Benkirane, 1998; Cheng & Rooryck, 2000; Haan, 2001; Haan, Van Heuven, Pacilly, & Van Bezooijen, 1997; Gryllia, Cheng & Doetjes, 2016; Hadding-Koch, 1961; Hadding-Koch & Studdert-Kennedy, 1964; Ishihara, 2005; Iivonen, 1998; Kitagawa, 2005; Sadat Tehrani, 2008, 2011; Uldall, 1962; Yang, Gryllia, Doetjes & Cheng, 2016 September) and globally, for example, in the form of a raised register and/or the absence of F0 downtrend (Bolinger, 1982; Geluykens, 1986; Haan, 2001; Haan et al, 1997; Inkelas & Leben, 1990; Lindsey, 1985; Sadat Tehrani, 2008, 2011; Thorsen, 1980; Vaissière, 1983).…”
Section: Prosody Of Interrogativesmentioning
confidence: 99%